2018
DOI: 10.1021/acs.inorgchem.8b00271
|View full text |Cite
|
Sign up to set email alerts
|

Hydride Conformers of the Nitrogenase FeMo-cofactor Two-Electron Reduced State E2(2H), Assigned Using Cryogenic Intra Electron Paramagnetic Resonance Cavity Photolysis

Abstract: Early studies in which nitrogenase was freeze-trapped during enzymatic turnover revealed the presence of high-spin (S = 3/2) electron paramagnetic resonance (EPR) signals from the active-site FeMo-cofactor (FeMo-co) in electron-reduced intermediates of the MoFe protein. Historically denoted as 1b and 1c, each of the signals is describable as a fictitious spin system, S′ = 1/2, with anisotropic g′ tensor, 1b with g′ = [4.21, 3.76, ?] and 1c with g′ = [4.69, ∼3.20, ?]. A clear discrepancy between the magnetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(85 citation statements)
references
References 25 publications
8
75
2
Order By: Relevance
“…Spectroscopic investigations have provided the spin state of various intermediates in the Lowe-Thorneley kinetic model, notably for this report, E 0 , E 2 , and both E 4 (4H) and E 4 (2N2H). As recently established (47), not only E 0 but also the E 2 intermediates have a total spin S = 3/2, while the two E 4 intermediates have S = 1/2 (6). Therefore, calculations were performed for the observed S = 3/2 spin state (E 0 and E 2 ) and the two S = 1/2 (E 4 ) states within the BS approach (16).…”
Section: Bs-dftmentioning
confidence: 65%
“…Spectroscopic investigations have provided the spin state of various intermediates in the Lowe-Thorneley kinetic model, notably for this report, E 0 , E 2 , and both E 4 (4H) and E 4 (2N2H). As recently established (47), not only E 0 but also the E 2 intermediates have a total spin S = 3/2, while the two E 4 intermediates have S = 1/2 (6). Therefore, calculations were performed for the observed S = 3/2 spin state (E 0 and E 2 ) and the two S = 1/2 (E 4 ) states within the BS approach (16).…”
Section: Bs-dftmentioning
confidence: 65%
“…Two 1 H nuclei (H 1 : a iso = 24.3 MHz, T = [−13.3, 0.7, 12.7] MHz; H 2 : a iso = 22.3 MHz, T = [10.7, −12.3,1.7] MHz) are assigned as Fe−( μ -H)−Fe moieties. 9a The 1 H signals are believed to arise from bridging, as opposed to terminal hydrides, due to the approximate rhombic symmetry of the dipolar tensor; a point−dipole model predicts a dipolar tensor of approximate axial symmetry for a terminally bound hydride. 49…”
Section: Resultsmentioning
confidence: 99%
“…[76] It seems not inconceivable that these two distinct EPR signals, 1b and 1c, could correspond to the E 2 -hyd and E 2 -nonhyd models suggested in this work. The study by Lukoyanov et al [26] demonstrated that the state with the 1b EPR signal likely to a hydride state at the E 2 redox level based on the known photoreactivity of metal hydrides. It was furthermore shown by photolysis of 1b that a photogenerated version of 1c (1c*) can form that was suggested to be a different hydride isomer.…”
Section: Discussionmentioning
confidence: 99%